Cartilage-sparing surgery for melanoma of the external ear. Issue 1 (January 2019) - Harrison, Conrad; Wade, Cian; Potter, Matthew; Cassell, Oliver
Summary: Background: The excision of melanoma of the external ear poses a challenge to surgeons, who must achieve adequate oncological control while minimising impact on form and function. Cartilage-preserving surgery is an attractive option, as it leaves behind a scaffold for immediate reconstruction with a variety of techniques including full-thickness skin grafts (FTSGs) and local flaps. This manuscript will review the literature comparing cartilage-sparing surgery with composite excision of the skin and the cartilage for the treatment of auricular melanoma. We report the results of a 17 year experience of using both techniques, together with sentinel node biopsy at our centre. Methods: A structured review of MEDLINE and EMBASE was conducted to evaluate all studies reporting local recurrence or survival rates for melanoma of the external ear treated with cartilage-preserving surgery. A retrospective review of all patients undergoing wide local excision (WLE) and sentinel lymph node biopsy (SLNB) for auricular melanoma at our centre between 2000 and 2017 was performed. Results: Of 40 patients identified, 29 underwent cartilage-preserving surgery with no local recurrences or evidence of perichondral involvement. There was one local recurrence out of 11 patients who had their cartilage excised. There were no significant differences in recurrence rates or melanoma-specific survival rates when comparing cartilage-preserving and cartilage-sparing surgery. Our results are supported by the literature review, which suggests that cartilage-sparing surgery is gaining acceptance as a safe practice.